Causes of Zoom Fatigue in Teachers During The New Normal During The New Normal Time - Octavariny, Raisha; Ningsih, Fadlillah Widya; Panjaitan, Delita Hayanti; Bangun, Sri Melda; Pardede, Junita (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Zoom fatigue is fatigue, anxiety, or worry resulting from overuse of virtual video conferencing platforms. Teachers who spend more time a day with online teaching activities experience significantly more stress, which can cause teachers to experience Zoom fatigue events. This study uses a quantitative method with a cross sectional design. The population in this study were all teachers at public senior high school 1 Lubuk Pakam, totaling 74 teachers and a sample of 42 teachers. The data was collected using questionnaires and interviews and the data was processed using the chi-square test which aims to determine the factors associated with the occurrence of Zoom fatigue in teachers during the COVID-19 pandemic. The results showed that there was a relationship between the variable length of exposure and the incidence of Zoom fatigue (0.011) < (0.05), a relationship between the technology problem variable and the incidence of Zoom fatigue (0.022) < (0.05) and the relationship between student factor variables and incidence of Zoom fatigue (0.005) < (0.05).Teachers said that they felt physically and emotionally exhausted while teaching online using the Zoom. The results of this study are expected to be taken into consideration by teachers to take time to stretch for 10-20 minutes after online teaching activities and provide time for the body and mind to rest for a moment looking at the computer/laptop screen.